Hull-Compatible Underwater IPT System with Enhanced Electromagnetic–Thermal Performance for USVs - Qingyu Zhao; Songyan Niu; Ziyun Shao; Linni Jian (Energies)
With the growing use of unmanned surface vehicles (USVs) for underwater exploration, efficient wireless charging solutions like inductive power transfer (IPT) are crucial for addressing power limitations. This paper presents a novel IPT system for USVs and introduces a systematic design approach for optimizing magnetic couplers. The proposed design addresses three critical challenges: misalignment tolerance, lightweight construction, and thermal safety, which are intricately linked through a magnetic field. In terms of misalignment, this paper demonstrates that the coil length is a key factor in determining misalignment tolerance. For a lightweight design, replacing the ferrite plate with ferrite bars can significantly reduce the weight of the coupler without causing core saturation. The design is further validated through a two-way coupled electromagnetic–thermal simulation. The results reveal that, with proper thermal management, the system avoids thermal risks in underwater environments compared to air. Finally, a 3 kW prototype is constructed and tested in fresh water, achieving 55 V and 50 A wireless charging at an 85.7% full-load dc-to-dc efficiency, thus confirming the practicality and performance of the design.